2006
DOI: 10.1080/13651820500540956
|View full text |Cite
|
Sign up to set email alerts
|

Increased intra-abdominal pressure: is it of any consequence in severe acute pancreatitis?

Abstract: Development of organ dysfunction in SAP could be associated with increased IAP. Grade III increase of IAP should be considered as an indicator for revision of treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
3
10
0
2
Order By: Relevance
“…14 However, in the present study, we only found a significant association between an increase in IAP and a variety kinds of clinical variables related to the process of SAP, such as the need of surgical intervention, vasoactive drugs and mechanical ventilation, the presence of pathogenic microorganisms and so on which is in consistent with several previous studies. 5,7,16,17 Differently, only a correlation with the need of vasoactive drugs could be found with respect to APP which means only patients with cardiovascular dysfunction presented lower APP in the first 72 h. This might mainly be because during the early phase of SAP, most patients even those with greatly increased level of IAP are still capable to maintain a reasonable APP level through increasing the level of MAP so that they could maintain sufficient visceral perfusion to avoid severe ischemia.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…14 However, in the present study, we only found a significant association between an increase in IAP and a variety kinds of clinical variables related to the process of SAP, such as the need of surgical intervention, vasoactive drugs and mechanical ventilation, the presence of pathogenic microorganisms and so on which is in consistent with several previous studies. 5,7,16,17 Differently, only a correlation with the need of vasoactive drugs could be found with respect to APP which means only patients with cardiovascular dysfunction presented lower APP in the first 72 h. This might mainly be because during the early phase of SAP, most patients even those with greatly increased level of IAP are still capable to maintain a reasonable APP level through increasing the level of MAP so that they could maintain sufficient visceral perfusion to avoid severe ischemia.…”
Section: Discussionmentioning
confidence: 63%
“…Several years before, the World Society of Abdominal Compartment Syndrome (WSACS) reviewed the literature and reached a consensus about the definitions of intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS) 4 and the technique for the measurement of intra-abdominal pressure (IAP). So far, several studies about IAH/ACS and its clinical relevance in SAP patients have been published [5][6][7][8] and the association of elevated IAP and high occurrence rates of organ dysfunction and death has been proved for several times although most of these studies did not adopt the standard technique and definition of IAH/ACS recommended by WSACS in 2006. 4 But for abdominal perfusion pressure (APP), which is defined as mean arterial pressure (MAP) minus IAP and proposed as an accurate predictor of visceral perfusion 9 in IAH/ACS patients, no study about its clinical relevance in SAP patients has been published yet.…”
Section: Introductionmentioning
confidence: 99%
“…Pupelis et al reported an elevated IAP during the first 3-5 days, and in patients with a favorable outcome a decrease from day 5 onwards [14]. De Waele et al reported that IAH developed after a median of 1 day, and was maximal on the second day.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of the same group 2 years later [6] revealed that obesity (defined as a body mass index of =30 kg/m 2 ) carries a significant 2.6-fold higher risk for development of SAP, and up to a 4.6-fold higher risk for complications. Pupelis and coworkers [7] found increased intra-abdominal pressure (=25 cmH 2 O), which is related to body weight, to be a risk factor for early organ dysfunction, and therefore they recommended monitoring of intra-abdominal pressure in patients with SAP.…”
Section: Prognostic Modelsmentioning
confidence: 99%